Assessing the Impact of Microfinancing on Economic Growth in Papua Province: An Analysis of KUR and UMi Programs (2019-2022) - Pisi Bethania Titalessy; Radian Januari Situmeang; Rahmat Rahmat; Mellyanti Eka Putri (International Journal of Applied Business and International Management, 2024)
Credit plays a vital role in supporting economic growth by aligning with development priorities to promote equitable outcomes. The People's Business Credit (KUR) and Ultra Microfinancing (UMi) programs are government initiatives designed to support Micro, Small, and Medium Enterprises (MSMEs) in Papua by providing financing for working capital and investment. Although the distribution of KUR and UMi in Papua has shown consistent annual growth, their contribution at the national level remains relatively small. This study examines the impact of these programs on economic growth in Papua Province from 2019 to 2022 using quantitative analysis and panel data regression. Findings reveal that KUR distribution, while significantly increased in Jayapura City, has a minimal impact on economic growth, as indicated by an R-squared value of 0.0058. The statistically insignificant coefficients for KUR and UMi suggest their limited contribution to economic development. External factors such as infrastructure and government support are likely more influential, underscoring the need to enhance program accessibility and explore broader determinants of Papua's economic growth. Recommendations include enhancing program accessibility and exploring other variables influencing Papua's economic dynamics.